2020
DOI: 10.1007/s10157-020-01854-3
|View full text |Cite
|
Sign up to set email alerts
|

New insight into podocyte slit diaphragm, a therapeutic target of proteinuria

Abstract: Dysfunction of slit diaphragm, a cell–cell junction of glomerular podocytes, is involved in the development of proteinuria in several glomerular diseases. Slit diaphragm should be a target of a novel therapy for proteinuria. Nephrin, NEPH1, P-cadherin, FAT, and ephrin-B1 were reported to be extracellular components forming a molecular sieve of the slit diaphragm. Several cytoplasmic proteins such as ZO-1, podocin, CD2AP, MAGI proteins and Par-complex molecules were identified as scaffold proteins linking the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 129 publications
1
65
0
8
Order By: Relevance
“…Podocytes are the largest intrinsic cell in the kidney.Early podocyte damage is reversible.Once the damaging factor is removed,the cytoskeleton proteins are repaired, and the foot processes still form a cross-connected pattern to perform their functions; however, if the damaging factor continues to act on podocytes,the podocyte damage irreversible [7][8] .The worst consequence is that the proliferative capacity of the podocytes is limited. Once damage occurs, podocytes cannot continue to perform their functions through self-compensation, forming a vicious circle and accelerating the damage of other podocytes, ultimately leading to the occurrence and development of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes are the largest intrinsic cell in the kidney.Early podocyte damage is reversible.Once the damaging factor is removed,the cytoskeleton proteins are repaired, and the foot processes still form a cross-connected pattern to perform their functions; however, if the damaging factor continues to act on podocytes,the podocyte damage irreversible [7][8] .The worst consequence is that the proliferative capacity of the podocytes is limited. Once damage occurs, podocytes cannot continue to perform their functions through self-compensation, forming a vicious circle and accelerating the damage of other podocytes, ultimately leading to the occurrence and development of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to understand the effect of PAR2 on the regulation of slit diaphragm protein expression. A decrease in the protein level of nephrin, a key molecule forming a molecular sieve of the slit diaphragm, 38 was not restored by AZL in SHRSP.ZF rat kidney, though podocin was increased. The imbalance in the expression of these slit diaphragm proteins may be involved in unresolved proteinuria in AZL‐treated SHRSP.ZF rats.…”
Section: Discussionmentioning
confidence: 88%
“…Numerous studies with naturally-occurring polyphenols have shown that a direct blockade targeting podocyte EMT ameliorates podocyte injury and proteinuria [ 23 , 40 ]. In addition, podocyte slit diaphragm has been a therapeutic target of proteinuria [ 5 , 41 ]. This study found that the polymethoxylated flavone tangeretin inhibited EMT process in diabetic podocytes and diabetic mouse kidneys.…”
Section: Discussionmentioning
confidence: 99%